2009
DOI: 10.1590/s0034-89102009000200014
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between physical and psychosocial demands of work associated to low back pain

Abstract: OBJECTIVE:To examine the interaction between physical and psychosocial demands of work associated to low back pain. METHODS:Cross-sectional study carried out in a stratifi ed proportional random sample of 577 plastic industry workers in the metropolitan area of the city of Salvador, Northeast Brazil in 2002. An anonymous standard questionnaire was administered in the workplace by trained interviewers. Physical demands at work were self-rated on a 6-point numeric scale, with anchors at each end of the scale. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 18 publications
1
14
0
6
Order By: Relevance
“…The analysis captured two factors, characterizing dynamic work with load handling and correlates (factor 1: load-lifting, standing posture of work, using muscle strength with arms or hands, working with arms raised above shoulder height, working with trunk rotation, physical pressure with both hands on the work's object, and inclined torso) and static work with repeatability (factor 2: general motionless posture of work, not walking, repetitive movements with the hands, and sitting posture). Both factors presented high theoretical plausibility and were used as the independent variables of physical demands at work 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis captured two factors, characterizing dynamic work with load handling and correlates (factor 1: load-lifting, standing posture of work, using muscle strength with arms or hands, working with arms raised above shoulder height, working with trunk rotation, physical pressure with both hands on the work's object, and inclined torso) and static work with repeatability (factor 2: general motionless posture of work, not walking, repetitive movements with the hands, and sitting posture). Both factors presented high theoretical plausibility and were used as the independent variables of physical demands at work 31 .…”
Section: Discussionmentioning
confidence: 99%
“…From these academic products, among others, some epidemiology articles were published on epidemiological prevalence of MSDs in this population 6 ; interaction between physical and psychosocial demands on the occurrence of low back pain 31 ; leisure physical activities and MSDs 32 ; interaction between physical fitness and physical demands at work on the occurrence of MSDs 33 ; validity and reproducibility of self-registration of the physical demands at work 34 ; and factors associated with MSDs in workers of this industry 21 . This latest exploratory study found an association between these diseases and female sex, psychosocial demands, and job dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados do presente estudo fortalecem o pressuposto do modelo de Karasek 12 que estabelece que o trabalho sob condições de baixo controle e alta demanda (alta exigência) é prejudicial à saúde. Assim, a associação positiva entre o trabalho de alta exigência e DME nos membros inferiores, membros superiores e dorso corrobora os achados de outros estudos que investigaram os aspectos psicossociais do trabalho (utilizando o modelo demanda-controle) e DME 3,7,8,9,21,29,30 . Alguns estudos também encontraram associação entre trabalho ativo e DME 9,21 .…”
Section: Discussionunclassified
“…Only the 2007 data were used in the analysis due to a signifi cant reduction in the benefi ts between 2005 (24,239) and 2007 (10,839) and the fact that the team of medical experts who were paid per case examination was replaced with experts from the Brazilian Social Security Administration.…”
Section: Methodsmentioning
confidence: 99%
“…10 Nursing providers and oil workers showed a high prevalence of low back pain. 9,13 Both occupations require constant weight bearing.…”
Section: Introductionmentioning
confidence: 99%